Sublethal effects of aged oil sands–affected water on white sucker (Catostomus commersonii). (2nd February 2015) - Arens, Collin J.; Hogan, Natacha S.; Kavanagh, Richard J.; Mercer, Angella G.; Kraak, Glen J. Van Der; van den Heuvel, Michael R.
Abstract: To investigate impacts of proposed oil sands aquatic reclamation techniques on benthic fish, white sucker ( Catostomus commersonii Lacépède, 1803) were stocked in 2 experimental ponds—Demonstration Pond, containing aged fine tailings capped with fresh water, consistent with proposed end‐pit lake designs, and South Bison Pond, containing aged unextracted oil sands material—to examine the effects of unmodified hydrocarbons. White sucker were stocked from a nearby reservoir at both sites in May 2010 and sampled 4 mo later to measure indicators of energy storage and utilization. Comparisons were then made with the source population and 2 reference lakes in the region. After exposure to aged tailings, white sucker had smaller testes and ovaries and reduced growth compared with the source population. Fish introduced to aged unextracted oil sands material showed an increase in growth over the same period. Limited available energy, endocrine disruption, and chronic stress likely contributed to the effects observed, corresponding to elevated concentrations of naphthenic acids, aromatic compounds in bile, and increased CYP1A activity. Because of the chemical and biological complexity of these systems, direct cause–effect relationships could not be identified; however, effects were associated with naphthenic acids, polycyclic aromatic hydrocarbons, ammonia, and high pH. Impacts on growth have not been previously observed in pelagic fishes examined in these systems, and may be related to differences in sediment interaction. Environ Toxicol Chem 2015;34:589–599. © 2014 SETAC